Mortality trends of traumatic brain injuries in the adult population of the United States: a CDC WONDER analysis from 1999 to 2020 - Muhammad Hamza Dawood; Yusra Fazli; Sejal Lund; Shurjeel Uddin Qazi; Rija Tahir; Areehah Zafar Masood; Aiman Azam Qureshi; Saleha Safdar; Heraa Zaheer; Muhammad TayyabMuzaffar Chaychi (BMC Public Health)
Abstract Background Traumatic Brain Injury (TBI) is a critical public health issue in the United States, contributing significantly to morbidity, mortality, and healthcare costs. Accounting for a substantial proportion of injury-related deaths and disabilities, TBI impacts a wide demographic, with particularly high incidence rates among young and elderly populations. Despite earlier declines, recent years have seen an uptick in TBI-related fatalities. This study aimed to evaluate the patterns and geographical disparities in mortality related to TBI among the adult population in the United States. Methods We examined the death certificates sourced from the Centers for Disease Control and Prevention Wide-Ranging Online Data for Epidemiologic Research (CDC WONDER) database to identify adults in whom TBI was documented as an underlying or contributing cause of death between 1999 and 2020. Age-adjusted mortality rates (AAMRs) per 100,000 individuals and annual percent change (APC) were computed and stratified based on year, gender, race/ethnicity, and geographic region. Results Between 1999 and 2020, 1,026,185 TBI-related deaths occurred among adults aged ≥ 25 years. The AAMR remained stable from 22.2 in 1999 to 22.3 in 2007, followed by an insignificant decline to 21.5 in 2010, and a steeper significant subsequent increase to 24.6 in 2020. Men had consistently higher AAMR than women from 1999 (men: 35.6; women: 11.1) to 2020 (men: 38.8; women: 11.9). The 85 + years age group had the highest AAMR 118.5 trailed by 75–84-year age group at 53.2. American Indian or Alaska Native adults had the highest AAMR (31.9) followed by White (24.4). South had the highest AAMR (25.3), followed by West (22.7). Non-metropolitan areas consistently had higher mortality rates compared to metropolitan areas. Conclusions Following a brief period of stability in TBI-related mortality from 1999 to 2010, there has been a subsequent increase of 1.3% per year in mortality till 2020. Notable geographic and demographic disparities persist, underscoring the need for further research and precise health policy interventions to better understand and address these differences.